A variable separation method for the calculation of the reliability of construction - Nguyen Van Pho (Vietnam Journal of Mechanics)
In this paper, a variable separation method for determining the reliability of construction is proposed. Therefore, the reliability is a multiplication of two probabilities: The probability of the occurrence of load and the probability of construction in the condition the load has a determined value.